Association between life-style behaviors and health outcomes in Adventist and non-Adventist adolescents in Mexico: a pilot study - Maria Elena Acosta Enríquez; Felipe Javier Uribe Salas; Juha Baek; Jenny Patricia Sierra Archbold; Genny Carrillo (BMC, 2019)
Abstract Background Identifying lifestyle-related health predictors affecting adolescent behaviors is a matter of interest and study for diverse audiences, including the religious sphere. The Adventist religion recommends their followers to adopt a healthy diet, adequate rest, physical activity, sufficient water intake, and non-use of addictive substances such as alcohol, tobacco, and drugs, as well as fostering faith and hope to give meaning to life. Methods A cross-sectional and observational study was conducted among adolescent students aged 13 to 19 years old in Montemorelos City, Nuevo León, Northern Mexico, between September 14, 2017 and February 13, 2018. This study included 363 Mexican adolescents, consisting of 202 Adventists and 161 non-Adventists. The binomial logistic regression analysis was performed to examine the relationships between religious affiliation and life-style behaviors and evaluate the effect of life-style behaviors on health outcomes by religious affiliation. Age, gender, type of residence, and place of birth were controlled. Results We found that Adventist adolescents were more likely to be watching TV for 2 h or less per day (p < 0.001), have enough sleeping time for 7 h or more (p < 0.001), go to bed early at 11 o'clock or before (p < 0.001), and have breakfast (p = 0.006) than non-Adventist adolescents significantly. It indicates that Adventist students are more likely to have healthier life-style behaviors than non-Adventist students. The multiple binomial regression models showed that in the group of Adventist adolescents sporting activity and hours watching TV were significantly associated with obesity risk (p = 0.001) and risky eating patterns (p = 0.044), respectively, controlling for age, gender, type of residence, and place of birth. No relationship was found between life-style behaviors and health outcomes in non-Adventist adolescents. Conclusions Religious affiliation could serve as a predictor of healthy behaviors among adolescents. This study concluded that Adventist adolescents are more likely to have a healthier lifestyle behavior than non-Adventist adolescents and various health-related behaviors were specifically identified among Adventist participants.